The effects of using games on efl students' speaking performances in the classroom - Nguyễn Thị Mỹ An (Trường Đại học Trà Vinh, 2019)
This research is carried out to find out non- English majors students’ learning English speaking skill at Tra Vinh University from students and teachers’s point of views. Then, some solutions will be generated from the teachers to overcome the problems and provide some suggestions, implications for the improvement of speaking teaching by using games.